Extracorporeal Membrane Oxygenation in Congenital Diaphragmatic Hernia - Rafat, Neysan; Schaible, Thomas (Frontiers in Pediatrics, 2019)
Congenital diaphragmatic hernia (CDH) is characterized by failure of diaphragmatic development with lung hypoplasia and persistent pulmonary hypertension of the newborn (PPHN). If conventional treatment with gentle ventilation and optimized vasoactive medication fails, extracorporeal membrane oxygenation (ECMO) may be considered. The benefits of ECMO in CDH are still controversial, since there are only few randomized trials demonstrating the advantages of this therapeutic option. At present, there is no precise prenatal and/or early postnatal prognostication parameter to predict reversibility of PPHN in CDH patients. Indications for initiating ECMO include either respiratory or circulatory parameters, which are also undergoing continuous refinement. Centers with higher case numbers and the availability of ECMO published promising survival rates, but data on long-term results, including morbidity and quality of life, are rare. Survival might be influenced by the timing of ECMO initiation and the timing of surgical repair. In this regard a trend towards early initiation of ECMO and early surgery on ECMO exists. The results concerning the cannulation modes are similar and a consensus on time limit for ECMO runs does not exist. The use of ECMO in CDH will continue to be evaluated, and prospective randomized trials and registry network are necessary to help answering the addressed questions of patient selection and management.